African Swine Fever Seroprevalence in Chad's Seemingly Healthful Pig Farming - Talita J; F. Ndongo; Nkea F. Andrew (African Journal of Pig Farming, 2025)
Introduction: ASF is an infectious disease that was initially identified in Kenya. It is brought on by a virus that is a member of the Asfivirus genus and Asfarviridae family. reported in central Africa and in eastern and southern Africa, where the virus is known to infect wildlife. In October 2010, Chad first encountered ASF. It was reported in four provinces in less than four months. The ASF virus would have first entered these several Chadian provinces due to biosecurity failures, inadequate disease control, unregulated animal transportation, marketing, and processing. Purpose: The aim of this study is to ascertain the seroprevalence of the ASF virus in Chad's ostensibly healthy pig farms. Material and Method: The study was carried out in the cities of Ndjamena, Mayo Kebbi East, and Chari Baguirmi provinces between September 2021 and September 2022. 492 farmers who had previously registered for ASF were the first to be counted. 198 of them agreed to take part in the research. In order to detect antibodies against the ASF virus, 345 sera were gathered and examined using the competition ELISA technique. The R Studio program was used to analyze the interview data and the serological findings. Results: In Mayo Kebbi East and Chari Baguirmi, the seroprevalences were 12.10 percent and 33.33%, respectively. The seroprevalence in the cities ranged from 10.10% to 33.33%. It was 61.53% in the boroughs and cantons. Eight districts, including Darda, Digo, Dogoré, Kabalaye, Malam-Sadi I, Malam-Sadi II, Tchinvogo, and Toukra-Massa, had seroprevalences above 30%, with respective rates of 44%, 61.53%, 50%, 33.33%, 45.45%, 50%, and 100%. The wet season, the types of pig farms (16.78%), the pigsty floor, and the lack of litter in the pigsties were all associated with changes in seroprevalence. Male seroprevalence was 19.23%; the highest rate, 78.52%, was observed in the 0–4 month age group. Conclusion: Although there are no obvious clinical symptoms, this investigation showed that the ASF virus is present in Chadian pig farms. Poor farming techniques and inadequate biosecurity controls would sustain the virus's presence in farms. The study offers evidence that ASF does, in fact, circulate throughout Chadian pig farms. An in-depth investigation of the factors influencing the circulation of the virus of the disease ASF is necessary since the lack of a vaccination against the disease is the cause of the increasing variances in seroprevalence in the various study sites.